Out-of-body experiences: interpretations through the eyes of those who live them - Moix, Jenny; Nieto, Isabel; De la Rua, Anna Yue (Frontiers in Psychology, 2025)
IntroductionOut-of-body experiences (OBEs) are primarily characterized by the sensation of the self being located outside one's physical body. The complexity of this phenomenon has led researchers to propose various theories to explain it, including physiological, psychological, and non-local consciousness theories. The objective of this study is to directly explore the interpretations of individuals who have experienced this phenomenon firsthand.MethodThe study employed a qualitative descriptive design with a phenomenological interpretive analysis approach, using in-depth semi-structured interviews. The sample comprised 10 participants without mental disorders or neurological and/or vestibular pathologies. The factors studied were predisposing, precipitating, phenomenological, consequential, and interpretive.ResultsAll participants agreed that their experience was not only real but described it as more vivid and authentic than everyday reality. Four participants had no explanation for their experience, while one interpreted it in physiological terms. The remaining five explained their experiences using terms like “other planes or dimensions” and “universal consciousness,” aligning with some authors who use concepts such as “non-local” or “expanded consciousness” to address OBEs.DiscussionThe findings suggest that, given that most participants refer to explanations that go beyond what is commonly understood as consciousness, theories of non-local consciousness could be enriched by incorporating these experiential perspectives.